Application of Time Series Analysis in Archaeology - Cheng, Quan; Lei, Xiaohe; Zhong, Xitong (Transactions on Environment, Energy and Earth Sciences, 2024)
Time series analysis is a statistical method widely used in archaeology to study changing patterns of ancient human activity. By analyzing these patterns, researchers can reveal how ancient civilizations interacted with their environment and developed and evolved. Radiocarbon dating, a classic application of time series analysis in archaeology, determines the age of ancient artifacts by measuring radiocarbon decay in samples. In addition, archaeologists have used time series analysis to study material and cultural changes in ancient societies, such as the evolution of pottery styles and the analysis of tree annual rings in environmental archaeolog.